Effects of in ovo feeding of vitamin C on embryonic development, hatching process, and chick rectal temperature of broiler embryos - Du, Shan; Zhou, Jianchuan; Ao, Xiang; Zhu, Yufei (Frontiers in Veterinary Science, 2025)
Maternal nutritional status plays a crucial role in embryonic development and has persistent effects on postnatal chicks. Vitamin C (VC) plays an important role in embryonic and postnatal development involved in nutri-epigenetics. The present study was conducted to investigate the effects of in ovo feeding (IOF) of VC on embryonic development, egg hatching time, and chick rectal temperature. Trial 1 was conducted under normal incubation conditions without the IOF procedure and was designed to analyze the characteristics of embryonic development and establish the scoring standards for yolk absorption and the rupture of the shell membrane. The results showed that the relative weight of the embryo and residual yolk and the organ indexes were reliable indicators of embryonic development. Yolk absorption was scored 0, 1, 2, 3, and 4, with a higher score indicating more complete absorption. In addition, the rupture of the shell membrane was divided into two cases: YES and NO. Trial 2 included three groups, control (CON), normal saline (NS), and vitamin C (VC), and was designed to detect the effects of IOF of VC on the indicators in trial 1, as well as the plasma biochemical indicators. At embryonic age 11 (E11), each egg in the CON group was non-injected, each egg in the NS group was injected with 0.1 mL of sterile normal saline, and each egg in the VC group was injected with 0.1 mL of sterile normal saline containing 3 mg vitamin C. The whole day of E21 was evenly divided into three time periods: early (incubation hours 480–488), middle (incubation hours 488–496), and late (incubation hours 496–504). Among the CON, NS, and VC groups, the percentages of the early-hatched chicks (egg hatching time) were 29.31, 12.00, and 33.90%, respectively. The proportions of early and middle hatched chicks in these groups were 51.72, 42.00, and 38.27%, respectively. The rectal temperature of chicks was lower (p < 0.05) in the VC group than in the CON and NS groups. Compared to the NS group, the plasma biochemical indicators in the VC group showed significantly lower levels of alkaline phosphatase (ALP), total protein (TP), albumin (ALB), GLB, total bilirubin (TBIL), TBA, uric acid (UA), high-density lipoprotein cholesterol (HDL-C), and corticosterone (CORT) (p < 0.05). Additionally, alanine aminotransferase (ALT) had an increasing trend (p = 0.059) in the VC group. In conclusion, our data demonstrated that VC accelerated the hatching process and reduced chicks’ rectal temperature, which may be related to the improvement of liver function and changes in metabolism, as indicated by blood biochemical indicators.